2023
DOI: 10.1002/cncr.34838
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional survey examining clinician characteristics, practices, and attitudes associated with adoption of the 2019 American Society for Colposcopy and Cervical Pathology risk‐based management consensus guidelines

Abstract: BackgroundThe 2019 American Society for Colposcopy and Cervical Pathology (ASCCP) risk‐based management consensus guidelines are the most recent national guidelines for the management of abnormal cervical cancer screening tests. These guidelines benefit patients by concentrating testing and treatment in those at highest cervical cancer risk. Adoption of guidelines often occurs slowly, with few studies examining the factors associated with guideline‐adherent management of abnormal results.MethodsTo elucidate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The first was a national study of clinicians from various clinical settings. A full description of the methodology has been published elsewhere, 19 but briefly, participants were recruited to participate in a survey via email between March and August 2021 from the National Association of Nurse Practitioners in Women's Health, the American Society of Colposcopy and Cervical Pathology (ASCCP), and Dynata (an online market research firm). The second was a supplemental study using similar methodology but limited to clinicians practicing in federally qualified health centers; participants were recruited between October 2021 and July 2022.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first was a national study of clinicians from various clinical settings. A full description of the methodology has been published elsewhere, 19 but briefly, participants were recruited to participate in a survey via email between March and August 2021 from the National Association of Nurse Practitioners in Women's Health, the American Society of Colposcopy and Cervical Pathology (ASCCP), and Dynata (an online market research firm). The second was a supplemental study using similar methodology but limited to clinicians practicing in federally qualified health centers; participants were recruited between October 2021 and July 2022.…”
Section: Participantsmentioning
confidence: 99%
“…17 Adoption occurs slowly; research performed in 2022 found that 75% of clinicians had adopted guidelines released in 2012 but only one third had adopted updates released in 2019. 16,18,19 Hence, it is foreseeable that clinicians will become more accepting of primary HPV screening and initiating screening at age 25 years over time. Increased uptake of these guidelines could be achieved if multiple professional societies endorse the use of primary HPV testing as a primary screening strategy.…”
mentioning
confidence: 99%